Military Matters in the Visigothic Kingdom: Initial Considerations - Ruchesi, Fernando Carlos (2018)
Battles, as well as the information related to military matters, always have been an important part of Visigothic history – medieval and modern. Such information has been transmitted amongst various political circles and, partly because of that, there exists different interpretations of the most important events in the history of the Visigoths. Despite previous and lingering historiographical disagreements, most contemporary and near-contemporary sources of the period describe the Battle of Vouillé and its consequences as a catastrophic event for the Visigoths. The negative portrayal of the episode is magnified by two events that are present in most of the sources: the death of King Alaric II (r. 485-507), and the theft of the royal Visigothic treasure. The aim of this essay is to analyze the manner in which sources composed in Hispania, compared as well as to sources written outside the Regnum, describe warfare and military events related to the Visigoths during the sixth and seventh centuries. To conceptualize the contemporary historiography of this major event, I will focus on the possible character of the audiences and the authorial intentions (political, ideological, and cultural) behind these fragments of military information.